PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT KELURAHAN PABEAN, KECAMATAN PEKALONGAN UTARA, KOTA PEKALONGAN TENTANG FILARIASIS LIMFATIK - Bina Ikawati; Bambang Yunianto; Rr Anggun Paramita Djati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2010)
A study on Society's Knowledge, Attitude and Practice (KAP) focused on Lymphatic Filariasis in Pabean Village, Pekalongan Utara Sub District, Pekalongan City has been done with cross sectional method. There were 100 respondences. The results showed 38% of the respondences had insufficient knowledge, 46% had suficient knowledgeand 16% had good practice. Most of the respondences had good attitude (91%) and 93% respondence had goodpractice. There was significant correlation between knowledge and attitude, there was no correlation between attitude and practice and between knowledge and practice. Observation showed that there were many breeding places around houses like riol anused land.